Macrophage polarization: an important role in inflammatory diseases - Luo, Min; Zhao, Fukun; Cheng, Huan; Su, Mu; Wang, Yuanmin (Frontiers in Immunology, 2024)
Macrophages are crucial cells in the human body's innate immunity and are engaged in a variety of non-inflammatory reactions. Macrophages can develop into two kinds when stimulated by distinct internal environments: pro-inflammatory M1-like macrophages and anti-inflammatory M2-type macrophages. During inflammation, the two kinds of macrophages are activated alternatively, and maintaining a reasonably steady ratio is critical for maintaining homeostasis in vivo. M1 macrophages can induce inflammation, but M2 macrophages suppress it. The imbalance between the two kinds of macrophages will have a significant impact on the illness process. As a result, there are an increasing number of research being conducted on relieving or curing illnesses by altering the amount of macrophages. This review summarizes the role of macrophage polarization in various inflammatory diseases, including autoimmune diseases (RA, EAE, MS, AIH, IBD, CD), allergic diseases (allergic rhinitis, allergic dermatitis, allergic asthma), atherosclerosis, obesity and type 2 diabetes, metabolic homeostasis, and the compounds or drugs that have been discovered or applie to the treatment of these diseases by targeting macrophage polarization.